Resposta :
Explicação passo-a-passo:
2) 12-2•3 3) 5²•2 7) -5+20÷2 9) (-6+24)÷6
12-6 (5•5)•2 -5+10 18÷6
=6 25•2 =5 =3
=50
10) 8+(-2)•9 11) 100÷20•5 12) 3-10+18
8+(-18) 5•5 7+18
=-10 =25 =25
13) 22+3•(-5) 14) 35÷8-4
22+(-15) 4,3-4
=17 =0,3
2) 12-2.3 = 6
12-6
6
3) 5²×2 = 50
25×2
50
7) -5 + 20 ÷ 2 = 5
-5 + 10
5
9) (-6+24)÷6 = 3
18 ÷ 6
3
10) 8 + (-2) .9 = - 10
8 - 18
- 10
11) 100 ÷ 20 . 50 = 250
5000 ÷ 20
250
12) 3 - 10 + 18 = 11
21 - 10
11
13) 22 + 3 × (-5) = 7
22-15
7
14) 35 ÷ 8 - 4 = 0,375
4,375 - 4
0,375